EFEKTIVITAS PELAYANAN PUBLIK PEMBUATAN KARTUTANDAPENCARI KERJA MELALUI E-MAKARYO DI DINAS TENAGAKERJAKOTA SURAKARTA - Muthiah, Lina; Riris Sugiyarti, Sri (Solidaritas, 2025)
This study examines the effectiveness of the job seeker card application process at the Surakarta City Manpower Office. This study highlights how the Surakarta City Manpower Office has succeeded in meeting the needs of job seekers by providing maximum service in processing applications. Despite the constraints of the phone operator's ability, instability of demand, especially during peak times, the Surakarta City Manpower Office has maintained the completion of job seeker card applications on time, ensuring that job seekers receive their cards without delay. This study uses the theory of Effectiveness according to William N Dunn (2021) namely efficiency, adequacy, equity, responsiveness and accuracy. Then this study uses qualitative methods, including interviews with job seekers and staff, to collect information about the service delivery process. The results of the study indicate that the Surakarta City Manpower Office's commitment to efficiency and user-centered services has resulted in a positive experience for job seeker card applicants. Users reported receiving adequate direction and support during the job seeker card application process, which has fostered trust and engagement. Overall, this study shows that the Surakarta City Manpower Office in terms of service effectiveness is good and can meet the needs of the community. This study underlines the importance of effective public service delivery in improving the accessibility of employment resources for job seekers, contributing to the goals of economic growth and broader community welfare in Surakarta.